Species of Fusarium Isolated from River and Sea Water of Southeastern Spain and Pathogenicity on Four Plant Species - Palmero, D (Plant disease, 2009)
Species of Fusarium were isolated from water samples collected from the Andarax River and coastal sea water of the Mediterranean in Granada and Almería provinces of southeastern Spain. In total, 18 water samples were analyzed from the Andarax River, and 10 species of Fusarium were isolated: Fusarium anthophilum, F. acuminatum, F. chlamydosporum, F. culmorum, F. equiseti, F. verticillioides, F. oxysporum, F. proliferatum, F. solani, and F. sambucinum. In addition, five species were isolated from 33 sea water samples from the Mediterranean Sea: F. equiseti, F. verticillioides, F. oxysporum, F. proliferatum, and F. solani. When considering the samples by their origins, 77.8% of the river water samples yielded at least one species of Fusarium, with F. oxysporum comprising 72.2% of the total isolates. In the case of marine water, 45.5% of the samples yielded at least one species of Fusarium, with F. solani comprising 36.3% of the total isolates. The pathogenicity of 41 isolates representing nine of the species collected from river and sea water during the study was evaluated on barley, kohlrabi, melon, and tomato. Inoculation with F. acuminatum, F. chlamydosporum, F. culmorum, F. equiseti, F. verticillioides, F. oxysporum, F. proliferatum F. solani, and F. sambucinum resulted in pre- and post-emergence damping off. Pathogenicity of Fusarium isolates did not seem to be related to the origin of the isolates (sea water or fresh water). However, the presence of pathogenic species of Fusarium in river water flowing to the sea could indicate long-distance dispersal in natural water environments